2006
DOI: 10.1007/s10979-006-9055-7
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making about volitional impairment in sexually violent predators.

Abstract: The Kansas v. Hendricks (1997) decision, in which the Supreme Court authorized post-sentence civil commitment for certain sex offenders, appeared to be constitutionally legitimized by limiting the class of offenders eligible for this special form of civil commitment to those who are “unable to control” their dangerousness. Nowhere in the available record, however, did the Court elucidate what they meant by this notion of volitional impairment. This study sought to examine factors that legal professionals (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Specifically, in the mental abnormality trial, offenders who opt for jury trials are two times more likely to win than their counterparts who opt for bench trials. This result is consistent with prior judge and jury decision-making studies (Kalven et al, 1966; Mercado et al, 2006) that find juries to be more lenient than judges in their rulings. Although the significance of this criminal justice factor is unlikely to impact the assessments for mental abnormality conducted by psychiatric examiners, it could impact the way examiners prepare their testimony.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Specifically, in the mental abnormality trial, offenders who opt for jury trials are two times more likely to win than their counterparts who opt for bench trials. This result is consistent with prior judge and jury decision-making studies (Kalven et al, 1966; Mercado et al, 2006) that find juries to be more lenient than judges in their rulings. Although the significance of this criminal justice factor is unlikely to impact the assessments for mental abnormality conducted by psychiatric examiners, it could impact the way examiners prepare their testimony.…”
Section: Discussionsupporting
confidence: 90%
“…Substance abuse, however, which is a factor linked to the impairment of behavioral control in physiological and neuroscience research (Fillmore, Marczinski, & Bowman, 2005; Lundqvist, 2005), was not found to be significant in these volitional impairment judgments. Mercado et al (2006) also found that the jury-eligible undergraduates were least likely to judge the defendant as having a mental disorder (50.1%), followed by legal professionals (63.7%), and then psychologists (63.9%).…”
Section: Evaluations Of the Civil Commitment Screening Processmentioning
confidence: 91%
See 1 more Smart Citation
“…In the United States, 20 states and the federal government have enacted SVP legislation since 1990 . Though statutory language differs across states, SVP commitment generally requires a history of sexual offending, a mental abnormality with evidence of volitional impairment, and a link between the mental abnormality and an elevated risk to commit future sexual violence (Kansas v. Hendricks, 1997;Mercado et al, 2006;Miller et al, 2005). New Jersey, for example, defines people subjected to SVP commitment (SVPs) as those with a history of sexual violence who "suffer from mental abnormalities or personality disorders which make them likely to engage in repeat acts of predatory sexual violence if not treated for their mental conditions" (N.J.S.…”
Section: Evaluating Selection For Sexually Violent Predator Commitmenmentioning
confidence: 99%
“…The VR videos are shot 10 Previous experimental research that investigated the impact of defendant characteristics such as race and mental illness on trial verdicts provided mock trial transcripts to be read by the evaluators. The race of the victim or defendant is manipulated using photographs and names (Mossiere, Maeder and Pica 2018;Maeder, Mossiere and Cheung 2012), or evaluators were given vignettes that described the offender and the circumstances of the case (Mercado, Bornstein and Schopp 2006). Some studies showed videos of mock trials where the trial conditions, such as eyewitness evidence, has been manipulated by the experimenters (Jones et al 2017).…”
Section: General Idea and The Contribution Of The Papermentioning
confidence: 99%